Effect of Elevated Temperature on Tomato Post-Harvest Properties - Vera Thole (MDPI AG, 2021)
The fleshy fruit of tomato (Solanum lycopersicum) is a commodity used worldwide as a fresh or processed product. Like many crops, tomato plants and harvested fruits are susceptible to the onset of climate change. Temperature plays a key role in tomato fruit production and ripening, including softening, development of fruit colour, flavour and aroma. The combination of climate change and the drive to reduce carbon emission and energy consumption is likely to affect tomato post-harvest storage conditions. In this study, we investigated the effect of an elevated storage temperature on tomato shelf life and fungal susceptibility. A collection of 41 genotypes with low and high field performance at elevated temperature, including different growth, fruit and market types, was used to assess post-harvest performances. A temperature increase from 18–20 °C to 26 °C reduced average shelf life of fruit by 4 days ± 1 day and increased fungal susceptibility by 11% ± 5% across all genotypes. We identified tomato varieties that exhibit both favourable post-harvest fruit quality and high field performance at elevated temperature. This work contributes to efforts to enhance crop resilience by selecting for thermotolerance combined with traits suitable to maintain and improve fruit quality, shelf life and pathogen susceptibility under changing climate conditions.